PENGENDALIAN JAMUR Saprolegnia sp PADA TELUR IKAN TAWES (Puntius javanicus) MENGGUNAKAN EKSTRAK DAUN BUNGA TAHI AYAM (Tagetes erecta L) - Farah Diana; Shela Rahmita; Sufal Diansyah (JURNAL PERIKANAN TROPIS, 2017)
Tawes (Puntius javanicus) is one of the freshwater fish species that has economic value in Aceh. One of the obstacle in tawes fish breeding is Saprolegnia sp. fungus that attacks tawes fish eggs. The necessary solutions  was needed to resolve fungal infection by using Tagetes erecta L. Therefore this research was very important to control fungal infections on fish eggs Saprolegnia sp.. This study used Randomized Complete Design with four treatments and three raplications for each treatments. The treatment in this study namely P0 = P1 = ppm, 40 ppm, P2 = 50 ppm, P3 = 60 ppm, and P4 = 70 ppm. The parameters observed in this research is the prevalence of eggs hatchability rate, eggs growth and water quality. The results of this study showed that the highest value of tawes eggs hatchability (prevalence) found in treatment 3 (P3 = 60 ppm) was 53.33% and the lowest value was present in control treatment (P0 = 0 ppm) was 36.66%. The reasults of eggs hatchability rate (HR) show the highest values found in treatment 2 (P2 = 50 ppm) of 95.66% and the lowest value is present on the control (P0 = 0 ppm) of 45.66%. On the egg development stage shows that there is a embryogenesis process starts from cleavage, morula, blastula, gastrula, organogenesis to become larvae. Water quality during the research shows that water temperature range were 29.2-30oC, and DO water range were 3.6-4.8 mg/l.